EVALUATION OF NATIONAL WOUND CARE CLINIC STANDARD IN INDONESIA: A PRE ELIMINARY STUDY - Sari, Mutmainnah; Muhtar, Trini Andini; Yusuf, Saldy (Jurnal Luka Indonesia, 2018)
Background: There is increasing number wound care nurses in Indonesia, following increasing number of private wound care clinic with different standard. Currently, national wound care clinic standard has been developed Indonesia which consisted 5 main standards and 27 sub standards. However, the validity remain unclear. Objective: The objective of this study was to evaluated content validity regarding clarity and relevancy. Methods: This was a cross sectional study, involved wound care nurses using purposive sampling technique. Eligibility criteria of partisipants were wound care nurse. Results: 36 nurses participate in this study (20, 55.6% female), mayority graduated form university (23, 63.9%) with experience as wound care nurse (mean, Â± SD; 9.00, 6.84) and daily working hours 4-8 hours (14, 38.9%). Content validity index focuss on clarity and relevance of national wound care clinic standard. From the result of content validity index (CVI) test can be concluded sub standard which has value